Vertebrate palaeontology - Benton, M. J. (Michael J.); John Wiley & Sons (Hoboken, NJ : Wiley, 2024)
"Vertebrate Palaeontology, 5th Edition provides a complete account of the evolution of vertebrates, including the macroevolutionary trends and drivers that have shaped their organs and body plans. In the fifth edition of this popular text, the author has again added numerous recent examples of breakthrough discoveries as well as the researchers who made them, connecting students with the excitement of a new fossil find. Richly illustrated with cladograms of all major vertebrate taxa, its phylogenetic focus makes it an up-to-date source of vertebrate evolution. A strong macroevolutionary focus highlights the key transitions such as terrestrialisation, endothermy, flight and impacts of mass extinctions on biodiversity. The ecological drivers behind the origin of chordates, origin of vertebrates, origin of limbs, origin of jaws, terrestrial limbs, feathers and hairs, bird and mammal innovations are described in detail along with the fossil record. The didactical features have been enhanced and include new functional and developmental feature spreads, key questions and extensive references to useful web sites"--
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Vertebrates, Fossil; Vertebrates; Fossils; Zoology